Growth Performance, Lipid Profile, and Fat Deposition of Broilers Fed Avocado and Carrot Leaf Extract - Merry Muspita Dyah Utami; Aryanti Candra Dewi; Niati Ningsih; Faiz Bilhaqqi Ridlo Maulana; Setya Islamianda (ANIMAL PRODUCTION, 2026)
This study aimed to evaluate the effects of avocado leaf extract (AE) and carrot leaf extract (CE) on the nutrient intake, growth performance, blood lipid profile, and fat deposition of broilers. Different concentrations of AE and CE were used in this study, namely 2.5% and 5%. T0 = 100% standard diet (control); T1 = 95% standard diet + 2.5% AE + 2.5% CE; T2= 92.5% standard diet + 5% AE + 2.5% CE; and T3 = 92.5% standard diet + 2.5% AE + 5% CE. One hundred one-day-old broilers were randomly assigned to four groups with five replicates of five chickens each and were treated during the grower-finisher period, from 14 to 35 days of age. The results showed that up to 2.5% AE and CE in the diet increased protein intake, energy intake, carcass weight and percentage, and high-density lipoprotein (HDL) (P<0.05), but reduced feed conversion, low-density lipoprotein (LDL), cholesterol, abdominal fat weight, and the percentage of abdominal fat. Body weight was highest at 5% AE, while cholesterol and LDL levels were lowest at 5% CE (P<0.05). In conclusion, avocado and carrot leaf extract up to 2.5% significantly improved nutrient intake, growth performance, and blood profile, and reduced fat deposition in broilers.